2020
DOI: 10.1021/acs.jpclett.0c02065
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Responses of Breast Cancer Cells to Substrates of Varying Stiffness Revealed by Single-Cell Measurements

Abstract: How cancer cells respond to different mechanical environments remains elusive. Here, we investigated the tension in single focal adhesions of MDA-MB-231 (metastatic breast cancer cells) and MCF-10A (normal human breast cells) cells on substrates of varying stiffness using single-cell measurements. Tension measurements in single focal adhesions using an improved FRET-based tension sensor showed that the tension in focal adhesions of MDA-MB-231 cells increased on stiffer substrates while the tension in MCF-10A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 48 publications
(86 reference statements)
0
9
0
Order By: Relevance
“…They found that cholangiocyte differentiation was regulated by matrix proteins and stiffness properties, and revealed the roles of ERK and Rho-associated protein kinase (ROCK) during the differentiation process. In another study, Tian et al [80] mimicked the matrix stiffness of different tissues from soft brain to stiff bone using PA substrates and probed the mechanical responses of breast cancer cells against diverse stiffnesses using magnetic tweezers and advanced imaging techniques. To overcome the inherent limitations of a continuous elastic substrate, substrates consisting of micropillars were developed.…”
Section: Matrix Stiffness-cell Interaction Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…They found that cholangiocyte differentiation was regulated by matrix proteins and stiffness properties, and revealed the roles of ERK and Rho-associated protein kinase (ROCK) during the differentiation process. In another study, Tian et al [80] mimicked the matrix stiffness of different tissues from soft brain to stiff bone using PA substrates and probed the mechanical responses of breast cancer cells against diverse stiffnesses using magnetic tweezers and advanced imaging techniques. To overcome the inherent limitations of a continuous elastic substrate, substrates consisting of micropillars were developed.…”
Section: Matrix Stiffness-cell Interaction Modelsmentioning
confidence: 99%
“…In another study, Tian et al . [80] mimicked the matrix stiffness of different tissues from soft brain to stiff bone using PA substrates and probed the mechanical responses of breast cancer cells against diverse stiffnesses using magnetic tweezers and advanced imaging techniques. To overcome the inherent limitations of a continuous elastic substrate, substrates consisting of micropillars were developed.…”
Section: In Vitro Construction Of the Tumor Mechanical Microenvironmentmentioning
confidence: 99%
“…It was shown that the nanomechanics of tumor cells depends on the rigidity of the substrate. Metastatic breast cancer cells are able to adapt to the stiffness of the matrix, increasing their elasticity, which allows them to survive in tissues with varying rigidity [ 136 ]. A similar change in cell stiffness has also been demonstrated in bladder tumor cells [ 134 ].…”
Section: Nanomechanical Features That Provide Cancer Aggression and I...mentioning
confidence: 99%
“…Biophysical measurements comparing the mechanical responses of normal and cancer cells have proven that cancer cells seem to become more compliant than their normal counterparts. The increased deformability of malignant cells is directly related with an increased metastatic potential (Tian et al 2020 ). In cancer cells, a softer cytoplasm correlates with a less-organized cytoskeleton (Guck et al 2005 ; Cross et al 2007 ).…”
Section: Introductionmentioning
confidence: 99%